The SGLT2 Inhibitor Dapagliflozin Reduces Liver Fat but Does Not Affect Tissue Insulin Sensitivity: A Randomized, Double-Blind, Placebo-Controlled Study With 8-Week Treatment in Type 2 Diabetes Patients - Latva-Rasku A; Honka MJ; Kullberg J; Mononen N; Lehtimaki T; Saltevo J; Kirjavainen AK; Saunavaara V; Iozzo P; Johansson L; Oscarsson J; Hannukainen JC; et al. (AMER DIABETES ASSOC, 2022)
OBJECTIVE The aim of this study was to investigate tissue-specific effects of dapagliflozin on insulin sensitivity and liver and body fat in patients with type 2 diabetes. RESEARCH DESIGN AND METHODS This randomized, double-blind, parallel group, placebo-controlled study recruited 32 patients with type 2 diabetes. Enrolled patients were to have HbA(1c) 6.5-10.5% (48-91 mmol/mol) and >= 3 months of stable treatment with metformin, dipeptidyl peptidase 4 inhibitor, or their combination. Patients were randomized 1:1 to receive 10 mg dapagliflozin or placebo daily for 8 weeks. Before and after the intervention, tissue insulin sensitivity was measured using [F-18]-fluorodeoxyglucose and positron emission tomography during hyperinsulinemic-euglycemic clamp. Liver proton density fat fraction (PDFF) and adipose tissue volumes were assessed using MRI, and blood biomarkers were analyzed. RESULTS After 8 weeks, glycemic control was improved by dapagliflozin (placebo-corrected change in HbA(1c) -0.39%, P < 0.01), but whole-body glucose uptake was not increased (P = 0.90). Tissue-specific insulin-stimulated glucose uptake did not change in skeletal muscle, liver, myocardium, or white and brown adipose tissue, and endogenous glucose production remained unaffected. However, there were significant placebo-corrected decreases in liver PDFF (-3.74%, P < 0.01), liver volume (-0.10 L, P < 0.05), visceral adipose tissue volume (-0.35 L, P < 0.01), interleukin-6 (-1.87 pg/mL, P < 0.05), and N-terminal prohormone of brain natriuretic peptide (-96 ng/L, P = 0.03). CONCLUSIONS In this study, 8 weeks of treatment with dapagliflozin reduced liver PDFF and the volume of visceral adipose tissue in obese patients with type 2 diabetes. Although glycemic control was improved, no effect on tissue-level insulin sensitivity was observed.